Parental Evaluation of the Socio-Personal Adjustment of High Ability Students in a Cluster Grouping Program - María de los Dolores Valadez; Julián Betancourt; Triana Aguirre; Elena Rodríguez-Naveiras; África Borges (MDPI AG, 2022)
High ability students have differential cognitive characteristics that require a specific educational response to develop their full potential. Cluster ability grouping is one of the available approaches to respond to their training. One of the main criticisms of this teaching method, also supported by the big-fish-little-pond effect (BFLPE), is that high ability students may show a decrease in their self-concept. The aim of this research is to present the evaluation carried out by parents of primary school high ability students on the effect of an educational cluster grouping program on their personal and social adjustment, comparing these variables before the beginning of the school year and at the end of it. Approximately 100 students' parents of the Educational Centre for Highly Ability Pupils participated in the evaluation. The instrument used for the evaluation was the Socialization Battery (BAS-2) for parents. The results showed that parents observed some improvements, either due to an increase in the scales measuring positive socialization variables or a decrease in the scales measuring negative socialization variables. The most substantial improvements are found in the second and third grades. We conclude that the results do not support the big-fish-little-pond effect (BFLPE).